2019
DOI: 10.1186/s12938-019-0643-4
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic non-rigid Iterative Closest Point Algorithm for respiratory motion abdominal surface matching

Abstract: Surface registration is a one of the crucial and actual problems of computer aided surgery. This paper presents the modification of the non-rigid Iterative Closest Point Algorithm which takes into account an anisotropic noise model and landmarks as guided correspondence at the transformation step in every iteration. The presented approach was validated on human abdominal briefing surface data from a time-of-flight camera. We took the median of the resulting measures and the outcome is presented: the median of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The non-rigid registration has been widely researched in the past decade and can be applied to various dynamic shape reconstruction issues such as human motion capture which is utilized for the applications in VR, AR, and entertainment. Some studies reported to apply non-rigid ICP to the field of biomedical engineering such as tracking of respiratory motion abdominal surface [ 15 , 16 ]. However, there is no research to apply the non-rigid ICP for localizing the specific region on the body surface such as the auscultation area considering the individual difference of body shape.…”
Section: Introductionmentioning
confidence: 99%
“…The non-rigid registration has been widely researched in the past decade and can be applied to various dynamic shape reconstruction issues such as human motion capture which is utilized for the applications in VR, AR, and entertainment. Some studies reported to apply non-rigid ICP to the field of biomedical engineering such as tracking of respiratory motion abdominal surface [ 15 , 16 ]. However, there is no research to apply the non-rigid ICP for localizing the specific region on the body surface such as the auscultation area considering the individual difference of body shape.…”
Section: Introductionmentioning
confidence: 99%